New strong divisibility sequences - Du, Zhibin (Ars mathematica contemporanea, 2022)
We provide new families of divisibility and strong divisibility sequences based on some factorization properties of Chebyshev polynomials.
Keywords: Chebyshev polynomials; determinant; determinanta; polinomi Čebiševa; strong divisibility sequences; tridiagonal matrices; tridiagonalne matrike; zlahka deljiva zaporedja